Private service provision contributes to widespread innovation adoption among smallholder farmers: Laser land levelling technology in northwestern India - Subash Surendran-Padmaja; Martin C. Parlasca; Matin Qaim; Vijesh V. Krishna (Agricultural Water Management)
Small farms often face challenges in adopting indivisible technologies, such as agricultural machinery, which contrast with more easily divisible technologies like new seeds and fertilisers. This study investigates key institutional factors promoting the adoption of laser land levelling (LLL), a water-saving technology that has gained wide popularity among farmers in northwestern India. The main objective is to evaluate how individual private service providers, offering LLL on a rental basis, influence technology adoption among farmers. Plot-level data from 1661 farm households across 84 villages in Punjab and western Uttar Pradesh were collected and analysed to understand farmers’ technology perceptions and adoption decisions. Results from regression models show that access to a larger number of private service providers in the local context is associated with higher rates of LLL adoption, also after controlling for other farm, household, and contextual characteristics. The effect of private service provision on adoption is particularly pronounced among the smallest farms. These findings suggest that conducive institutional environments, tailored to the specific needs of different farm sizes, help to speed up innovation adoption. Our study is the first to show that individual service provision through private agents is a promising mechanism for inclusive technology adoption in the small-fam sector.